2020
DOI: 10.1002/jbm.b.34765
|View full text |Cite
|
Sign up to set email alerts
|

Tendon‐like tether formation for tongue‐base advancement in an ovine model using a novel implant device intended for the surgical management of obstructive sleep apnoea

Abstract: Obstructive sleep apnoea (OSA) is a serious debilitating condition with significant morbidity and mortality affecting almost one billion adults globally. The current gold standard in the non‐surgical management of airway collapse is continuous positive airway pressure (CPAP). However, non‐compliance leads to a high abandon rate (27–46%). While there are multiple sites of airway obstruction during sleep, the tongue base is recognized as the key player in the pathogenesis of OSA. Poor outcomes of current tongue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
(103 reference statements)
0
1
0
Order By: Relevance
“…To explore the pathogenesis of OSA patients, OSA animal models were established in different species, including dogs, rats and lambs. [21][22][23] OSA patients were characterised by inharmonious craniofacial structures, such as retrusive mandible and vertically overdeveloped mandible, which may cause a structural alteration of the UA and lead to different levels of obstruction. 24 Compared to previous OSA models, we found that rabbits were obligate nose breathers due to their epiglottis positioned rostrally to the soft palate.…”
Section: Discussionmentioning
confidence: 99%
“…To explore the pathogenesis of OSA patients, OSA animal models were established in different species, including dogs, rats and lambs. [21][22][23] OSA patients were characterised by inharmonious craniofacial structures, such as retrusive mandible and vertically overdeveloped mandible, which may cause a structural alteration of the UA and lead to different levels of obstruction. 24 Compared to previous OSA models, we found that rabbits were obligate nose breathers due to their epiglottis positioned rostrally to the soft palate.…”
Section: Discussionmentioning
confidence: 99%